Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1175/1520-0493(2000)128<1653:lwsaeo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Low-Wavenumber Structure and Evolution of the Hurricane Inner Core Observed by Airborne Dual-Doppler Radar

Abstract: The asymmetric dynamics of the hurricane inner-core region is examined through a novel analysis of high temporal resolution, three-dimensional wind fields derived from airborne dual-Doppler radar. Seven consecutive composites of Hurricane Olivia's (1994) wind field with 30-min time resolution depict a weakening storm undergoing substantial structural changes. The symmetric and asymmetric mechanisms involved in this transformation are considered separately. To zeroth order the weakening of the primary circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
275
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(311 citation statements)
references
References 42 publications
34
275
1
Order By: Relevance
“…The amplitude of the mesovortices weakened with height, and the wavenumber-1 pattern shifted to the upwind side of the azimuthal parent vortex flow dominated widely above a 4-km height. This vertical structure is similar to the observational results of Hurricane Olivia (1994), which revealed that the asymmetry in the inner core was dominated by an azimuthal wavenumber-2 feature below 3-km height and a wavenumber-1 feature above that height (Reasor et al 2000). The enhanced convective activities in the eastward side (Figs.…”
Section: Structure Of the Simulated Mesovorticessupporting
confidence: 89%
“…The amplitude of the mesovortices weakened with height, and the wavenumber-1 pattern shifted to the upwind side of the azimuthal parent vortex flow dominated widely above a 4-km height. This vertical structure is similar to the observational results of Hurricane Olivia (1994), which revealed that the asymmetry in the inner core was dominated by an azimuthal wavenumber-2 feature below 3-km height and a wavenumber-1 feature above that height (Reasor et al 2000). The enhanced convective activities in the eastward side (Figs.…”
Section: Structure Of the Simulated Mesovorticessupporting
confidence: 89%
“…Whether and by which means storms are detrimentally impacted by vertical shear on their periphery has not been well established. In most previous studies of vertical wind shear impacts on tropical cyclones, the ''detrimental'' shear was thought to be that existing over the core (the center and out to some specified radius) of the storm (Marks et al 1992;Franklin et al 1993;Reasor et al 2000;Black et al 2002;Corbosiero andMolinari 2002, 2003;Rogers et al 2003;Chan et al 2004;Braun et al 2006;Braun and Wu 2007;Chen et al 2006) and was often assumed to be horizontally uniform in modeling studies (Jones 1995;Frank andRitchie 1999, 2001;Wong and Chan 2004). For this study, we assume that the presence of an AEJ near the periphery of a storm is not necessarily detrimental to storm development.…”
Section: Vertical Shear and Increased Stabilitymentioning
confidence: 99%
“…Many have focused on the effects of non-trivial vertical wind shear across a developing or mature vortex (e.g. Frank and Ritchie, 1999;Reasor et al, 2000;Frank and Ritchie, 2001;Black et al, 2002;Schecter and Montgomery, 2003;Rogers et al, 2003;Reasor et al, 2004); others have examined the structure of vortex-wave 564 N. VAN SANG ET AL. Montgomery and Enagonio, 1998;Möller and Montgomery, 2000;Enagonio and Montgomery, 2001;Heymsfield et al, 2001;Braun, 2002;Hendricks et al, 2004;Montgomery et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%